Segmentation of Kuala Lumpur transit market based on the attitude of traveller towards travelling / Mohd Shahriman Shafein - Shafein, Mohd Shahriman (2015)
The Malaysian government has invested heavily to encourage modal shift from private vehicles to public transport, as severe problems arises from the usage of the former mode. The need of understanding human psychological factor toward transport modal shift has gained much interest from public transportation researchers, especially in rapidly-urbanised area such as Kuala Lumpur, Malaysia. This study aims to identify the socio-demographics and attitude characteristics of travellers that are "easy-toreach" and "hard-to-reach" based on their attitudes toward travelling. This is achieved by fulfilling the objectives which include an investigation into the key attitudinal factors and its relationship with the willingness to use transit, and the determination of market segments and positions in KL transit market. A questionnaire survey was designed and randomly distributed to travellers within Kuala Lumpur , Malaysia. Total response was 366 respondents. The study has found that six key attitudes are present within the thirty two attitudinal variables. Conclusion made from Structures Equation Modelling (SEM) analysis shows that Sensitivity to Safety & Privacy, Sensitivity to Stress & Comfort and Need for Fixed Schedule was significant in influencing travellers to use transit. Based on the loadings and level of significant, Sensitivity to Safety and Sensitivity to Stress & Comfort was chosen to construct the market segments, together with the dependent factor (Willingness to Use Transit). Eight segments were constructed and examined to identify the socio-demographics and attitude characteristics, and fifteen combination of market position was analysed . It is found that easy-to-reach segment consist of travellers who are least sensitive to safety and privacy, least sensitive to stress and comfort yet show the lowest willingness to use transit. It has the least desire for productivity and reliability, not sensitive to time and the most flexible with travel schedule. On the other hand, the hard-to-reach travellers have the highest sensitivity to safety and privacy, very high sensitivity to stress and comfort but show the highest willingness to use transit. It also has the highest desire for productivity and reliability, are the most sensitive to time and highest in the need for fixed schedule.